PROBLEMATIKA PENDIDIKAN DI INDONESIA - Nurul Afifah (Jurusan PGMI FTIK IAIN Metro Lampung, 2015)
Education in Indonesia quantitatively have achieved significant progress. It is can be proved by statistics that 67.24% of the population in Indonesia has been freed from illiteracy. But this success unfollowed by the success of output education. There are various problems of education became in Indonesia, for example : children’s moral decline of the nation, lacking work ethic, low skills, corruption and increased of unemployment intellectuals. At least, there are three factors causes the problem of education in Indonesia from the learning aspect, first; approach in learning, all this time education and learning just emphasizes on uniformity behavior, it hope be regularity, order and certainty. Second; curriculum change. Often curriculum change lead to confusion in determining the direction of teacher learning. and the third is the competence of teacher. The solution is. Should a teacher looking at students as a person who should be developed, and equipped with the solution of various problems of life, the ultimate goal of learning which includes cognitive, affective and psychomotor. The conventional and modern methods should be applied equally. A teacher should be master the four competencies, namely: pedagogical competence, personal competence, social competence, and professional competence. And the teacher should be a role model for their students.